The role of financial inclusion in moderating the incidence of entrepreneurship on energy poverty in Ghana - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2023)
This paper assesses the role of financial inclusion in moderating the incidence of entrepreneurship on energy poverty in Ghana. The assessment is made by using pooled data and two stage least squares. The exposition builds from the 7th (GLSS7) and 6th (GLSS6) rounds focusing on the Ghana Living Standards Survey (GSS, 2014, 2019) that is collected by the Ghana Statistical Service (GSS) from ten principal regions in the country. The findings show that entrepreneurship has an unconditional positive incidence on energy poverty while the interactive incidence between entrepreneurship and financial inclusion on energy poverty is negative. The corresponding financial inclusion policy thresholds that should be exceeded in order for financial inclusion to effectively moderate entrepreneurship for negative outcomes in energy poverty: (i) are between 0.154 and 0.280 index for the full sample; (ii) is between 0.187 index for the rural sub-sample; (iii) are between 0.200 and 0.333 index for the male sample. (iv) Thresholds are not computed for the rural and female sub-samples because at least one estimated coefficient that is needed for the computation of such thresholds is not significant. Policy implications are discussed. This study has complemented the existing literature by assessing how financial inclusion can be employed to influence the nexus between entrepreneurship and poverty in Ghana.
Keywords: D03; D12; D14; I32; Q41; 330; Energy poverty; Financial inclusion; Consumption poverty; Education; Household income